Pelocoris balius La Rivers (Hemiptera: Heteroptera: Naucoridae) in Florida: New Status of an Enigmatic Saucer Bug - Sites, Robert W. (Zootaxa, 2015)
The saucer bug subspecies Pelocoris femoratus balius La Rivers was described from east-central Florida and differs from the nominate subspecies by pronounced dark spotting on the fore femora, head, and pronotum. This subspecies is much less commonly encountered than is P. f. femoratus (Palisot de Beauvois), which occurs throughout Florida. Although both subspecies occur in the area, uncertainty about the taxonomic status of P. f. balius has persisted. I here elevate P. f. balius to full species status based on collections of both taxa from the same bodies of water in multiple counties and additional morphological differences to those given in the original description. A supplemental description, distribution map, and illustrations to distinguish between the two species are provided.